Enhanced Light Absorption of Silicon Nanotube Arrays for Organic/Inorganic Hybrid Solar Cells. (18th February 2014) - Jeong, Huisu; Song, Hui; Pak, Yusin; Kwon, Il Keun; Jo, Kyubong; Lee, Heon; Jung, Gun Young
<x xml:space="preserve">Abstract</x> By combining nanoimprint lithography technique and a two‐step lift‐off process, a Si nanotube array is fabricated and applied as a light absorber for n‐Si/PEDOT:PSS hybrid solar cells. The light is effectively trapped within the nanotubes and the device reveals a Jsc of 29.9 mA·cm−2 and a power conversion efficiency of 10.03%, which is an enhancement of 13.4% compared to the cell having the best‐known Si architecture of nanocones as a light absorber to date. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>